PP.88 Identification of Clinically Important Components of Maternal and Neonatal Composite Outcomes to Assess the Effect of Timing of Delivery in Women with Mild to Moderate Pre-Eclampsia at 34 to 37 Weeks. (26th April 2013) - Fong, F; Rogozinska, E; Allotey, J; Kempley, S; Shah, D; Thangaratinam, S
Abstract : Background: Pre-eclampsia is associated with maternal and neonatal morbidity and mortality. Delivery is often expedited to minimise maternal complications at the risk of prematurity-related complications in the baby. The important outcomes to be evaluated in the management of pregnant women with pre-eclampsia between 34 to 37 weeks gestation is unclear. Objective: To identify the clinically important components of maternal and neonatal composite outcomes in the management of women with mild to moderate pre-eclampsia between 34 to 37 weeks by a Delphi survey of experts. Methods: A two-generational Delphi method was used to prioritise the maternal and neonatal outcomes that are considered to be important in the timing of delivery in women with mild to moderate pre-eclampsia. Results: The maternal outcomes questionnaire was sent to 20 participants and the neonatal outcomes questionnaire to 24 participants. 18/20 participants (90%) responded in the first round for maternal outcomes and 18/24 participants (75%) for neonatal outcomes. In the second round 16/17 eligible participants (94%) responded for maternal outcomes and 18/18 participants (100%) for the neonatal outcomes. 21 maternal and 24 neonatal outcomes were evaluated in the first round and 17 maternal and 25 neonatal outcomes in the second round. We identified 17 and 17 components to be clinically important for development of the maternal and neonatal composite outcomes respectively. If accepted, we will be able to provide full details of the relevant outcomes. Conclusion: The composite maternal and neonatal outcomes will allow evaluation of the effect of intervention to reduce mortality and morbidity.